DEVELOPING DIGITAL GENDER-INCLUSIVE TEACHING MODULE FOR TENTH GRADERS IN THE INDONESIAN ELT CONTEXT - Setyawati, Yulia Fida (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2024)
Gender stereotypes and gender issues exist in English materials. Research investigating gender stereotypes in English learning materials in the Indonesian ELT context revealed gender issues focusing on male dominance. A need analysis was conducted at SMK Negeri 1 Gedangan to examine the current needs and conditions in the school environment. The result showed that gender bias and stereotypes exist in English materials. This research aims to develop gender-inclusive teaching module of Kurikulum Merdeka (Independent Curriculum) using AADIE for tenth grade students. An ADDIE research design serves as a guidance in developing the digital teaching module in this research. The expert validation resulted in a final score of 55 out of 100 which means the product is good to use with some minor revisions. After the revision process, the product was implemented to class X AK 1. The results of the product implementation showed good results in students' understanding of gender inclusiveness in reading and speaking skills. TPACK as a framework is used in this research since it helps teachers to combine content, pedagogy, and technology to create effective learning. Multimodal and scaffolding frameworks allow product development to fulfil students' and teachers' needs.